2020
DOI: 10.1101/2020.08.20.260190
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virucidal and antiviral activity of astodrimer sodium against SARS-CoV-2 in vitro

Abstract: An effective response to the ongoing coronavirus disease (COVID-19) pandemic caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) will require a range of complementary preventive modalities. The current studies were conducted to evaluate the in vitro SARS-CoV-2 antiviral activity of astodrimer sodium, a dendrimer with broad spectrum antimicrobial activity, including against enveloped viruses in in vitro and in vivo models, that is marketed for antiviral and antibacterial applications. We repo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…It is still not commercially available for the prevention of STIs in any countries. Furthermore, it also shows significant activity against other viruses, such as the novel coronavirus SARS-CoV-2 [ 172 ], enabling a fast-track development of tools to fight COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It is still not commercially available for the prevention of STIs in any countries. Furthermore, it also shows significant activity against other viruses, such as the novel coronavirus SARS-CoV-2 [ 172 ], enabling a fast-track development of tools to fight COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…The 32 amino groups present at the surface of this dendrimer were derivatized with sodium 1-(carboxymethoxy) naphthalene-3,6-disulfonate, thus generating a p( L -Lys) dendrimer with an anionic surface charge, with the commercial name astodrimer sodium. Paull et al evaluated the antiviral activity of SPL7013 and found that it inhibits replication of SARS-CoV-2 in Vero E6 cells when added to cells one hour prior to, or one hour post infection [ 67 ], in a way similar as observed previously for the inhibition of HIV [ 68 ]. Since it is a dendrimer-based antiviral compound, inhalability is possible, and the authors conclude that SPL7013 warrants investigation for nasal administration to aid in preventing viral transmission and that it could be useful in the treatment of SARS-CoV-2.…”
Section: Poly(amino Acid)-based Dendrimersmentioning
confidence: 99%
“…The nanoparticle formulation also demonstrates extended release of the drug which may offer opportunity for reduced administration frequency, further enhancing patient convenience [45]. Starpharma also have a dendrimer-based antiviral nasal spray, SPL7013, in development, the mode of action of which appears to be binding of the active agent to the virus spike protein and inhibiting its ability to enter host cells [46,47].…”
Section: Starpharma Long Acting Remdesivirmentioning
confidence: 99%